PMM.43 The Predictive Value of Urinary Albumin: Creatinine Ratio In Pregnancy. (9th June 2014) - Robb, AO; Ffrench-Constant, A; Morris, RK; Denison, FC; Stock, SJ
Abstract : Introduction: Current risk assessment guidelines for pre-eclampsia are unable to reliably predict adverse outcomes and thus inform management. This study investigated the association and predictive value of urinary albumin: creatinine ratio (ACR) in pregnancy for adverse outcomes. Methods: Demographic, clinical and biochemical data were collected, retrospectively, for 914 pregnant women who had an ACR test between December 2009 and February 2012. Fetal outcome and preterm delivery data were collected: other maternal outcomes were collected for a subset of 385 pregnancies. Odds ratios were used to investigate the association of ACR at two thresholds (30 and 60mg/mmol) with outcome. Sensitivity and specificity investigated the predictive ability. Proportions were compared using the Chi-square test. Results: In women with ACR > 30 mg/mmol the following outcomes were more frequent (P < 0.05): preterm delivery (38.2% vs. 10.5%), hypertension (95.7% vs. 69.4%), treatment with anti-hypertensives (71.3% vs. 30.2%), admission to maternal HDU (61.7% vs. 22.0%) and admission of the baby to neonatal unit (22.4% vs. 5.8%). There was a significant association between ACR > 30 mg/mmol and these outcomes (OR >1, 95% CI not crossing 1) but predictive ability was limited; specificity (73–96%) and sensitivity (31–66%). At a higher threshold, ACR >60mg/mmol did not demonstrate improved sensitivity (21–44%). Conclusion: Raised ACR appears to be associated with an increased likelihood of developing certain adverse outcomes. However the predictive ability is limited by poor sensitivity.